The Evaluation of the National Policy on Ease of Doing Business in Nigeria - Olagunju, Olasunkanmi Olusogo; Ikeolumba, Jonathan Obinna (European Scientific Journal, ESJ, 2019)
The difficulty of doing business in Nigeria has gained currency in the national discussion in a recent time. This research paper aimed to review the successes and failures in the implementation of the ease of doing business in policy. It examines the effects of the various programmes put in place for realization of the policy objectives. Having adopted secondary method of data collection, this paper therefore concludes that even though the policy has recorded some little degree of successes, the business climate in Nigeria is still far from friendly due to some implementation paradoxes that have beclouded the policy objectives. The paper will therefore proffer some policy recommendations that may be instrumental for the actualization of the policy objectives.